2001
DOI: 10.1182/blood.v98.9.2681
|View full text |Cite
|
Sign up to set email alerts
|

X-linked thrombocytopenia caused by a novel mutation ofGATA-1

Abstract: A family with recessive X-linked thrombocytopenia affecting 4 males in 2 generations, characterized by macrothrombocytopenia, profound bleeding, and mild dyserythropoiesis, is described. Microsatellite linkage analysis identified a region of the X chromosome including the GATA-1 gene, which encodes a critical transcription factor involved in erythrocyte and megakaryocyte development. By sequencing the entire coding region of GATA-1, a 2-base mutation was detected that results in a single amino acid substitutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
149
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(154 citation statements)
references
References 25 publications
3
149
0
2
Order By: Relevance
“…52 In particular, patients with the G208S alteration in GATA-1 accumulate large, immature megakaryocytes within their bone marrow and suffer from macrothrombocytopenia. 53 Similarly, expression of the V205G mutant of GATA-1 in place of the wild-type protein also leads to the generation of large, abnormal megakaryocytes both in vivo and in vitro. 20,54 As shown in this report, these latter mutant megakaryocytes express cyclin D1 at more than 20 times the amount found in GATA-1-deficient counterparts.…”
Section: Human Gata1 Mutations Have Differential Effects On Megakaryomentioning
confidence: 99%
“…52 In particular, patients with the G208S alteration in GATA-1 accumulate large, immature megakaryocytes within their bone marrow and suffer from macrothrombocytopenia. 53 Similarly, expression of the V205G mutant of GATA-1 in place of the wild-type protein also leads to the generation of large, abnormal megakaryocytes both in vivo and in vitro. 20,54 As shown in this report, these latter mutant megakaryocytes express cyclin D1 at more than 20 times the amount found in GATA-1-deficient counterparts.…”
Section: Human Gata1 Mutations Have Differential Effects On Megakaryomentioning
confidence: 99%
“…Vertebrate GATA-1 and Runx1 are coexpressed and have overlapping functions during hematopoiesis, including megakaryopoiesis (15)(16)(17)(18)(19)(20)(21)(22). In addition, in vitro studies have suggested that the GATA-1:Runx1 complex directs megakaryocyte differentiation (22).…”
Section: Srp and Lz Synergistically Activate The Crystal Cell Programmentioning
confidence: 99%
“…For instance, somatic mutations in the GATA1 gene, which result in the production of GATA1-⌬NT (or GATA1s), are a prerequisite for the onset of transient myeloproliferative disorder (TMD) and subsequent acute megakaryoblastic leukemia (AMkL) in Down syndrome patients (44). Similarly, GATA1 mutations in the N-finger domain were found in multiple cases with familial anemia and thrombocytopenia (45)(46)(47)(48). In the latter cases, the association potential of GATA1 with either FOG1 or GATAbox DNA was attenuated, indicating that the N-finger domain is important for the GATA1 activity.…”
Section: Discussionmentioning
confidence: 99%